2020
DOI: 10.3390/cells9020413
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Pancreatic β-Cell Differentiation and Functioning: The Influence of Mechanotransduction

Abstract: Embryonic and pluripotent stem cells hold great promise in generating β-cells for both replacing medicine and novel therapeutic discoveries in diabetes mellitus. However, their differentiation in vitro is still inefficient, and functional studies reveal that most of these β-like cells still fail to fully mirror the adult β-cell physiology. For their proper growth and functioning, β-cells require a very specific environment, the islet niche, which provides a myriad of chemical and physical signals. While the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 178 publications
(213 reference statements)
0
26
0
Order By: Relevance
“…In turn, this modification probably drags the decrease in TCA cycle and aerobic respiration observed in cells grown on nanosubstrates. Immunoblotting and morphological studies revealed same modifications in two distinct beta cell lines (βTC3 and INS1E), thus suggesting that it may be a general mechanism of beta cell adaptation to changes in substrate topography (Galli et al, 2020).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…In turn, this modification probably drags the decrease in TCA cycle and aerobic respiration observed in cells grown on nanosubstrates. Immunoblotting and morphological studies revealed same modifications in two distinct beta cell lines (βTC3 and INS1E), thus suggesting that it may be a general mechanism of beta cell adaptation to changes in substrate topography (Galli et al, 2020).…”
Section: Resultsmentioning
confidence: 75%
“…This phenomenon, i.e., the conversion of microenvironmental biophysical information into corresponding cellular responses, is defined as mechanotransduction: the extracellular matrix (ECM) configuration affects the assembly of integrin adhesion complexes (IAC) and their signaling. This impacts the nuclear architecture and mechanosensitive transcription factors, eventually leading to modifications of the cell program (Chen et al, 2014;Schulte et al, 2016;Galli et al, 2018Galli et al, , 2020Maffioli et al, 2018;Chighizola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic islet architecture with intra-islet cell-cell communication between β-cells and other endocrine cell types are essential for β-cell functionality and glucose responsiveness. During islet development, for proper β-cell lineage specification, differentiation and maturation, intact cell-cell (via intercellular adherents junctions: cadherins, connexins, and nectins) and cell-matrix (via mechanical cues through extracellular matrix (ECM) stiffness, topography, fluid shear forces, and geometry) interactions are crucial for coordinating and supporting cells [ 107 , 108 , 109 , 110 , 111 , 112 ]. The pancreas is considered a soft organ based on its ECM composition.…”
Section: Ipsc-derived Pancreatic β-Like Cellsmentioning
confidence: 99%